Cell analysis method - FUJIWARA KAZUHIKO; KAZAMI, SAYAKA; MARUYAMA YOSHIHIRO (2022)
A cell analysis method according to the present invention comprises: a mixing step (S11) for preparing a mixed solution by mixing cells as a subject, a metal ion solution, and a reducing agent; a metal microstructure generation step (S12) in which the metal ions in the mixed solution are reduced by the reducing action of the reducing agent in the mixed solution to generate a metal microstructure on the support, and cells or a cell-derived substance are adhered to the metal microstructure; a drying step (S13) of drying the support body after the metal microstructure generation step; a measurement step (S15) in which, after the drying step, the metal microstructure on the support is irradiated with excitation light, and the spectrum of Raman scattered light generated by irradiation with the excitation light is measured; and an analysis step (S16) for analyzing the cells on the basis of the spectrum of the Raman scattered light. As a result, a method is achieved in which a cell, which is a subject, can be easily